Konsentrasi Timbal (Pb) pada Kerang Kepah (Geloina expansa), Air, dan Sedimen Mangrove Desa Peniti Kabupaten Mempawah Kalimantan Barat - Sofiana, Mega Sari Juane; Safitri, Ikha; Apriansyah, Apriansyah; Irawan, Suhardi (Jurnal Sumberdaya Akuatik Indopasifik, 2023)
Heavy metal pollution and its hazards are global issues that need proper attention. Heavy metals are toxic to the environment and aquatic organisms. As a filter feeder, Kepah are able to absorb and accumulate heavy metal from the environment into their body. Kepah is edible bivalve that widely consumed because its potential nutritional value, so that the biotoxic effect in human are great concern. Peniti River has important roles for the coastal community, especially in Mempawah Regency. This area has been developed for various uses. These activities greatly influenced water condition and were considered as sources of pollution, including heavy metals. The aim of this study was to evaluate the Pb content in Kepah flesh, water, and sediment collected from the mangrove ecosystem area of Peniti Village. The sample collection and measurement of environmental parameters were carried out at two stations based on the presence of Kepah. The standard technique was used to quantify the Pb level in the samples. The analysis of Pb content was performed using an Atomic Absorption Spectrophotometer (AAS). The concentrations of Pb in the water and sediment samples were above the threshold. Meanwhile, the metal content of Pb in Kepah flesh was still below the maximum limit that had been determined. Therefore, Kepah from the mangrove ecosystem of Peniti Village, Mempawah Regency, were still good for consumption.